Social Media–Driven Language Shift Among Gen Z: Intergenerational Communication Gaps Between Private‑School Students and Parents in Mardan (Pakistan) (Journal of Asian Development Studies, 2025)
Language reflects identity, values, and generational belonging. In today's platform-driven culture, apps like Instagram, TikTok, Snapchat, and WhatsApp are accelerating linguistic change among Generation Z, reshaping vocabulary, orthography, and pragmatics while normalising abbreviations, emojis, and fluid code-switching. This study explores how such "platform vernaculars" shape everyday expression among private-school students in Mardan, Pakistan— where digital fluency intersects with strong local traditions—and how these shifts widen communication gaps with parents less embedded in social media. Using an exploratory qualitative sociolinguistic approach, the study analyses student language practices alongside parental perceptions to identify key features of Gen Z discourse (acronyms, emoji-based stance marking, English–Urdu/Pashto code-mixing, and translanguaging) and sites of intergenerational misrecognition (e.g., divergent views on tone, politeness, and affect). Findings indicate that students utilise platform-specific repertoires to convey cosmopolitan belonging and peer intimacy. At the same time, many parents perceive the same forms as vague, impolite, or exclusionary— creating friction rooted not in intent but in digital literacy gaps. Framed within a Global South pedagogical perspective, the study advocates bridging "digital–domestic" literacies through school initiatives and family workshops that foster shared metalinguistic awareness. By highlighting the sociolinguistic impact of social media in a Pakistani context, this work contributes to research on youth language change, intergenerational communication, and culturally responsive language education (see Table 1) (see Figure 1).